Desired Professional Development Pathways for Clinical Pharmacists. Issue 4 (11th February 2013) - ,; Shord, Stacy S.; Schwinghammer, Terry L.; Badowski, Melissa; Banderas, Julie; Burton, Michael E.; Chapleau, Christopher A.; Gallagher, Jason C.; Matsuura, Gregory; Parli, Sara E.; Yunker, Nancy
<x xml:space="preserve">Abstract</x> The 2012 American College of Clinical Pharmacy (ACCP) Certification Affairs Committee was charged with developing guidelines for the desired professional development pathways for clinical pharmacists. This document summarizes recommendations for postgraduate education and training for graduates of U.S. schools and colleges of pharmacy and describes the preferred pathways for achieving, demonstrating, and maintaining competence as clinical pharmacists. After initial licensure within the state or jurisdiction in which the pharmacist intends to practice, completion of an accredited PGY1 pharmacy residency is recommended to further develop the knowledge and skills needed to optimize medication therapy outcomes. An accredited PGY2 pharmacy residency should be completed if a pharmacist wishes to seek employment in a specific therapeutic area or practice setting, if such a residency exists. Clinical pharmacists intending to conduct advanced research that is competitive for federal funding are encouraged to complete a fellowship or graduate education. Initial certification by the Board of Pharmacy Specialties (BPS) or other appropriate sponsoring organizations should be completed in the desired primary therapeutic area or practice setting within 2 years after accepting a position within the desired specific therapeutic area or practice setting. Clinical pharmacists subsequently will need to meet the requirements to maintain pharmacist licensure and board certification. Traineeships, practice‐based activities, and certificate programs can be used to obtain additional knowledge and skills that support professional growth. Pharmacists are strongly encouraged to adopt a lifelong, systematic process for professional development and work with ACCP and other professional organizations to facilitate the development and implementation of innovative strategies to assess core practice competencies.